Tinjauan Al-Qur'an dan Hadits Tentang Pemimpin dan Persyaratanya (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to delve deeper into the concept of leadership in Islam based on the verses of the Quran and the sayings of Prophet Muhammad (PBUH), as well as to determine the criteria that must be met by a leader in accordance with the teachings of Islam. The research methodology employed is textual analysis of the Quranic verses and hadiths related to this theme. This study highlights the importance of leadership based on the principles of Islam in carrying out the responsibility of leading the community. The results of the analysis indicate that the Quran and the sayings of the Prophet contain numerous guidelines regarding the qualities that should be possessed by a good and trustworthy leader. These criteria include integrity, justice, wisdom, responsibility, and exemplary behavior